D&AD09 : the best advertising in the world. - British Design & Art Direction (Association) (Cologne : Taschen, 2010)
Featuring the latest D&AD award-winning work in the fields of: Ambient, Art Direction, Book Design, Branding, Broadcast Innovations, Digital Installations, Direct, Environmental Design, Graphic Design, Illustration, Magazine & Newspaper Design, Mobile Marketing, Music Videos, Online Advertising, Packaging Design, Photography, Poster Advertising, Press Advertising, Product Design, Radio, TV & Cinema Advertising, TV & Cinema Crafts, Viral, Websites, Writing for Advertising, and Writing for Design.
Keywords: Adverteren; Reclame